Transfer of motor and perceptual skills from basketball to darts - Rienhoff, Rebecca; Hopwood, Melissa; Fischer, Lennart; Strauss, Bernd; Baker, Joe; Schorer, Joerg (Frontiers in Psychology, 2013)
The quiet eye is a perceptual skill associated with expertise and superior performance; however, little is known about the transfer of quiet eye across domains. We attempted to replicate previous skill-based differences in quiet eye and investigated whether transfer of motor and perceptual skills occurs between similar tasks. Throwing accuracy and quiet eye duration for skilled and less-skilled basketball players were examined in basketball free throw shooting and the transfer task of dart throwing. Skilled basketball players showed significantly higher throwing accuracy and longer quiet eye duration in the basketball free throw task compared to their less-skilled counterparts. Further, skilled basketball players showed positive transfer from basketball to dart throwing in accuracy but not in quiet eye duration. Our results raise interesting questions regarding the measurement of transfer between skills.